La gota madre: Revelación del río hablador - Camargo Reyes, Camila Andrea (2025)
Exploring Lima’s most polluted river, the Rímac, from its role in pre-Hispanic worldview to its current condition in the city, means immersing into its physical, symbolic and cultural deterioration. Along this journey, there emerges, like a revelation silenced by the metropolis: The Mother Drop, a proposal transformed into an installation project that seeks to restore the river as a being, reinforcing the bond between humans and “Earth Beings” (De la Cadena, 2015), a concept that recognizes the agency of natural entities. Through a ceramic filtration system, it proposes a methodological collaboration with the riverbed and natural elements to create a sustainable alternative for the river’s symbolic recovery; while at the same time inviting reflection on the act of purifying its waters towards the future.